Comparison of Mini-Percutaneous Nephrolithotomy (Mini-PCNL) and Retrograde Intrarenal Surgery (RIRS) for Management of Lower Calyceal Renal Calculi - Umair Khan; Muhammad Sohail; Maryam Dahri; Muhammad Bilal Abdullah; Muhammad Arif Khan; Muhammad Waqas (Medical Journal of South Punjab, 2024)
Objectives: In terms of surgery time, pain level (visual analogue score), analgesic need, hemoglobin drop, and hospitalization, a prospective evaluation of the results of retrograde intrarenal operation and mini-PCNL is presented.Methodology: It was comparative cross-sectional study. The 50 participants in this study, 25 of who had RIRS and 25 of who had MINIPERC, were urologists for two years and had lower calyx stones up to 20 mm in size. Data analysis was done through SPSS version 25.Results: The percentage of stones cleared by Miniperc and RIRS was 100% and 96%, correspondingly. One patient in the RIRS group needed a one-month retreatment. Complications during and after surgery, as well as hospitalization were not statistically significant for either group. Operative duration in the Miniperc category was shorter (P=0.003). In the RIRS group, there was a decrease in hemoglobin drop (P